Moonlighting Proteins – Nature's Swiss Army Knives. (November 2017) - Jeffery, Constance J.
The human body is a complex biological machine with billions of cells and vast numbers of biochemical processes – but our genome only contains 22, 000 protein-encoding genes. Moonlighting proteins provide one way to increase the number of cellular activities. Moonlighting proteins exhibit more than one physiologically relevant biochemical or biophysical function within one polypeptide chain. Already more than 300 moonlighting proteins have been identified, and they include a diverse set of proteins with a large variety of functions. This article discusses examples of moonlighting proteins, how one protein structure can perform two different functions, and how the multiple functions can be regulated. In addition to learning more about what our proteins do and how they work together in complex multilayered interaction networks and processes in our bodies, the study of moonlighting proteins can inform future synthetic biology projects in making proteins that perform new functions and new combinations of functions, for example, for synthesising new materials, delivering drugs into cells, and in bioremediation.